Samgar ben Anat onder die Rigters - Snyman, S. D. (HTS teologiese studies, 2004)
Samgar ben Anat among the JudgesShamgar ben Anath could be regarded as both isolated and ignored. He finds himself isolated between the two major judges, Ehud and Deborah, and for this reason is easily overlooked and ignored. Shamgar, although not an Israelite, should be considered as a judge in his own right. Shamgar is seen as the successor to Ehud. He has, as is the case with other judges, the responsibility of delivering the people and he makes use of whatever capabilities and skills he might possess. Theologically seen, one should rather regard it as Yahweh and the judges being simultaneously at work with Yahweh taking the most unlikely candidates with the most awkward weapons into his service to deliver his people time and again from the hardships of oppression.